2000
DOI: 10.1006/jfbi.2000.1361
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of temperature on the influence of dietary linolenic (18:3 n-3) and linoleic (18:2 n-6) acids on the gonadal recrudescence in Clarias batrachus (L.)

Abstract: During the late postspawning phase, freshwater catfish Clarias batrachus fed a diet rich in linseed oil (18 : 3 n-3) (LSO) and 13L : 11D photoperiod and at 28 C showed increases in ovarian weight and plasma levels of testosterone and oestradiol-17 , and in concentrations of free fatty acids (FFA), monoglycerides (MG), diglycerides (DG), triglycerides (TG), phospholipids (PL) and esterified cholesterol (CE) in the liver, plasma and ovary. In fish fed a diet rich in sunflower oil (18 : 2 n-6) (SFO) under the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 23 publications
4
4
1
Order By: Relevance
“…The present study indicated that dietary fatty acids play a determinant role in modulating the reproductive activity in the male African catfish, C. gariepinus during the pre-spawning phase. A significant increase in GSI as well as T and T3 in the C18 n-3 PUFA fed fishes showed that LSO plays a stimulatory role in gonadal recrudescence which is consistent with our earlier report (Acharia et al, 2000) in another catfish, C. batrachus. Since elevation in GSI by SO oil compared to basal diet was not statistically significant it was considered that this particular fatty acid had no effect on gonadal recrudescence at this phase.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study indicated that dietary fatty acids play a determinant role in modulating the reproductive activity in the male African catfish, C. gariepinus during the pre-spawning phase. A significant increase in GSI as well as T and T3 in the C18 n-3 PUFA fed fishes showed that LSO plays a stimulatory role in gonadal recrudescence which is consistent with our earlier report (Acharia et al, 2000) in another catfish, C. batrachus. Since elevation in GSI by SO oil compared to basal diet was not statistically significant it was considered that this particular fatty acid had no effect on gonadal recrudescence at this phase.…”
Section: Discussionsupporting
confidence: 92%
“…Since body weight remained unaltered (data not shown) in response to any of the experimental fatty acid supplemented diets, it is assumed that C18:3 n-3 or C18:2 n-6 or C12:0 had no impact on the somatic growth in this fish during the pre-spawning phase particularly. Similar observation was reported in the earlier studies performed in the Indian female catfish C. batrachus (Acharia et al, 2000(Acharia et al, , 2001. However, in this species the differential role of n-3 or n-6 PUFA for gonadal activity was temperature dependent.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Balance in the diet of both of n-3 and n-6 which are critical during organogenesis in embryos and larvae is required in the broodstock diet for optimum reproductive success of fish (Acharia et al, 2000;Bell et al, 1997;Nandi et al, 1999). Our results showed that n-3/n-6 ratios of all samples in PL and NL within a narrow range (0.44-1.80), with one exception in NL for African catfish ovary which had (9.23) value.…”
Section: Fatty Acids Ratiosmentioning
confidence: 99%